Hair loss in children in rural population - Manne, Vimala; Subhash Reddy, D. (International Journal of Research in Dermatology, 2019)
Background: Among children worldwide, dermatophyte infections are most common constituting a public health problem. The aim of the study is to determine the prevalence and causative agents of tinea capitis in school children attending primary school located in Hyderabad and to perform an analysis of risk factors associated with tinea capitis as the etiological factor. Methods: This is a school based, cross sectional, prospective study which was conducted in July 2015. This study was conducted in a school located near Hyderabad. Results: Out of 600 school children, 298 boys and 302 girls, 100 were diagnosed with a tinea capitis infection after clinical and microbiological examination, with an estimated prevalence rate of 15.0%. The most prevalent dermatophytes isolation in tinea capitis in children were Trichophyton verucosum (90), Trichophyton tonsurans (30), Trichophyton mentagrophytes (28), Microsporum audiouium (15), Trichophyton soudanese (9), Trichophyton violaceum (5), Microsporum ferrugineum (3), Trichophyton schoenleineii (3), Microsporum gallinae (2) and culture negative and KOH positive (10). Conclusions: This study concluded that the findings suggest that the practices resulting in entrenchment of dermatophyte infections and fungal infection. The promotion of public health action plan based on self hygiene education, which aimed to counteract the epidemiological burden specifically, and it should play an pivotal role in reduction of the prevalence in future of this common infection.